Non-destructive determination of the stiffness matrix of a laminated composite structure with lamb wave. (1st April 2020) - Yilmaz, C.; Topal, S.; Ali, H.Q.; Tabrizi, I.E.; Al-Nadhari, A.; Suleman, A.; Yildiz, M.
Abstract: This study presents a combined experimental and numerical study on the determination of the stiffness matrix of transversely isotropic thin laminated composite structures non-destructively with the use of group velocity measurements. The approach relies on the usage of A0 and S0 modes of Lamb waves, triggered the by pencil-lead break, which propagate in the composite material, and enables the evaluation of various elements of the stiffness matrix. It is proven that the experimental Lamb wave method can be reliably utilized for determining the components of the stiffness matrix, C ij . The results are validated with respect to those of mechanical characterization and finite element analysis.